Comparative Analysis of Operational Transconductance Amplifiers and Their Design Technologies - Simran Somal , Tripti Sharma (International Journal of Advanced Science and Technology, 2020)
This paper reviews about the various kind of operational amplifiers used for amplifying the signal or for other applications. Nowadays, Operational amplifiers are used in all streams like electronics, electrical, medical, image processing etc. So the requirement is to make an op-amp which will able to does all type of operations. Various kind of operational amplifiers are used like cascode amplifiers, folded cascode amplifiers, operational transconductance amplifiers etc. The basic requirement of operational amplifiers is it should have a high gain and low power consumption. For making the circuit with less power consumption, various techniques are used. The basic techniques are bulk driven technique, floating gate, input split stage, BD-MOS technique etc. The circuits which are used by authors basically built under 180nm technology with power supply of 0.5V.